The effects of foreign direct investment and trade openness on economic growth amid crises in Asian economies - Rabiul Hossain; Chandan Kumar Roy; Rima Akter (Universitas Islam Indonesia, 2022)
Purpose ― The main objective is to examine the effects of foreign direct investment and trade openness on economic growth (SDG-8.1) about economic growth amid crises in 30 Asian economies. Design/methodology/approach ― The effects of FDI and trade openness on economic growth in the Asian region are examined using the fixed-effects model, panel corrected standard errors (PCSE), and generalized method of moments (GMM) estimations. The study also measures the long-run effects of the estimates and the granger causality tests. Findings ― The findings revealed that both FDI and trade openness contribute to boosting economic growth in Asian economies, and the effect is also persistent in the long run. We also find that the Asian and global financial collapse shocks in 1997-1998 and 2008-2009, respectively, adversely affected the region's economic growth. Additionally, the economic growths of some Asian countries are below the targeted level set in SDG-8.1. Practical implications ― The Asian countries should adopt appropriate policy measures for encouraging the inflow of FDI and cross-border trade of goods and services as it is evident that the inflow of FDI and open trade will improve local human capital and technological capabilities of the industries, which will ultimately help to enhance stable economic growth. Originality/value ― This study is unique in accompanying the Asian financial crisis and world recession in studying the effects of FDI and trade openness on SDG-8.1 in Asian economies.